Formation and reactivity of the terminal vanadium nitride functionality - Tran, Ba L.; Krzystek, J.; Ozarowski, Andrew; Chen, Chung-Hsing; Pink, Maren; Karty, Jonathan A.; Telser, Joshua; Meyer, Karsten; Mindiola, Daniel J. (European Journal of Inorganic Chemistry, 2013)
The transformation of vanadium(III) azides, [(nacnac)V(N )-(X)] nacnac = [ArNC(CH)] CH, Ar = 2,6-(CHMe)C H; X = Ntol, where tol = 4-MeCH, n = 1; X = ArO, n = 2, to their corresponding vanadium(V) nitrides, [(nacnac)-V=N(X)], was investigated through an isotopic labeling crossover experiment. The nuclearity of the azide species is dependent on the size of the supporting ligand, X, with X = ArO, thus featuring a VN core with two μ-1,3- N bridging ligands across the VIII centers. SQUID magnetization studies and multifrequency, high-field EPR (HFEPR) experiments reveal the mononuclear azide complex to be consistent with an S = 1 system, while the dimeric azide system is weakly antiferromagnetically coupled with a spin singlet ground state and thermally accessible triplet and quintet states. These combined results suggest that the transformation of a vanadium(III) azide to a vanadium(V) nitride most likely occurs by a bimetallic mechanism, where Lewis bases inhibit N extrusion. Room-temperature generation of the nitride products from their corresponding azides can also be accomplished stoichiometrically with a Lewis acid, such as B(CF) , and catalytically, through an unsaturated vanadium(II) fragment, [(nacnac)V(Ntol)]. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.